Alternative protein sources from selected legumes and mushrooms in the development of high-protein instant soup for the elderly - Rajnibhas Sukeaw Samakradhamrongthai; Taruedee Jannu; Tussanun Tongboonchu; Wanalee Sangpimpa; Phatthamon Srichan; Orapan Sangsee; Gerry Renaldi; Preeyabhorn Detarun (Heliyon, 2024)
Elderly people are susceptible to malnutrition due to many factors. An essential public health priority is ensuring that seniors have appropriate nutrition to prevent and treat malnutrition and dehydration as well as fulfilling the nutrition necessity. This study was conducted to utilize selected legumes and mushrooms to develop a high-protein instant soup (HPIS) product that is nutritious and suitable for the consumption of the elderly. Black bean, along with oyster mushroom and split-gill mushrooms, exhibited considerable amounts of protein (19.13 ± 1.13, 2.77 ± 0.09, and 4.65 ± 0.61 g/100 g, respectively), calcium (2308.65 ± 113.07, 640.19 ± 0.80, and 743.89 ± 0.66, respectively), iron (40.84 ± 2.42, 7.31 ± 0.05, and 40.10 ± 2.15, respectively), and zinc (18.06 ± 1.07, 3.87 ± 0.03, and 26.23 ± 0.78, respectively) content, and were incorporated into the HPIS formula. Drum dryer rotation speed significantly affected the HPIS properties. The study on the effect of different rotation speeds (3, 5, 7, and 9 RPM) used during the drying process revealed the use of 7 RPM resulting in the soup product with considerable quality. The optimized HPIS formula, which was supplemented with minerals, was moderately liked (7.1–7.5) by the elderly consumer. The majority of the consumers accepted the product (97 %) and were interested in purchasing the product (91 %) if it was available on the market. Incorporating selected legumes and mushrooms resulted in a soup product containing nutrition conforming to the Thai recommended daily intake (RDI), possessing adequate physicochemical and sensory properties for the consumption of the elderly.